Tinggi Badan yang Diukur dan Berdasarkan Tinggi Lutut Menggunakan Rumus Chumlea pada Lansia - Etisa Adi Murbawani; Niken Puruhita; Yudomurti Yudomurti (MEDIA MEDIKA INDONESIANA, 2012)
Measured height and calculated height based on knee height using chumlea formula in elderlyBackground: Height is an important anthropometric measurement. Height calculation equation for elderly with dorsal deformity using knee height was developed by Chumlea. However, the equation is not appropriate for elderly in Asian population. The aim of this study was to compare measured height with calculated height based on knee height using Chumlea formula for elderly in Indonesia.Method: A cross sectional study was conducted in 86 elderly in geriatric outpatient clinic in Kariadi hospital, nursing home, and eldery integrated health service (posyandu lansia) in Semarang which were randomly selected in July-September 2009. The inclusion criteria were elderly without deformities and able to stand up straightly. Data collected were demography characteristics, height and knee height. Height was measured using microtoise, knee height was measured using knee calliper. Both microtoise and knee calliper had 0.1 cm accuracy. Data were analysed using Wilcoxon signed rank test.Result: Most samples were female, aged 59-88 years. The average age was 71±8.7 years. The average measured height in female and male subjects were 146.8±5.6 cm and 160.8±6.2 cm respectively. The average calculated height in female and male subjects were 154.3±7.03 cm and and 159.1±6.78 cm respectively. There was no different (p=0.077) in measured height and calculated height using Chumlea formula.Conclusion: There was no different in measured height and calculated height using Chumlea formula.Keywords: Elderly, height, knee height, nutritional assesmentABSTRAKLatar belakang: Tinggi badan merupakan salah satu indikator pengukuran antropometri yang penting. Persamaan perhitungan tinggi badan pada lansia (lanjut usia) dengan deformitas punggung telah dikembangkan oleh Chumlea. Persamaan yang ada saat ini tidak tepat untuk populasi Asia. Tujuan penelitian ini adalah mengetahui kesesuaian antara tinggi badan yang diukur dengan microtoise dengan perhitungan berdasarkan tinggi lutut menggunakan rumus Chumlea untuk lansia di Indonesia.Metode: Desain penelitian ini adalah belah lintang. Subyek penelitian adalah 86 (delapan puluh enam) lansia yang menjadi pasien rawat jalan Poliklinik Geriatri di RSUP Dr. Kariadi Semarang, lansia yang menjadi penghuni panti wredha dan lansia yang menjadi anggota posyandu lansia di Semarang pada bulan Juli-September 2009. Kriteria inklusi pasien adalah tidak ada deformitas pada struktur tubuh dan mampu berdiri tegak. Data yang dikumpulkan meliputi karakteristik demografi, tinggi badan dan tinggilutut. Tinggi badan diukur menggunakan microtoise, sedangkan tinggi lutut diukur menggunakan knee calliper dengan akurasi 0,1 cm. Analisis data menggunakan uji beda Wilcoxon signed rank test.Hasil: Sebagian besar subyek berjenis kelamin perempuan, dengan usia 59-88 tahun. Rerata umur subyek sebesar 71±8,7 tahun. Rerata tinggi badan perempuan dan laki-laki adalah 146,8±5,6 cm, dan 160,8±6,2 cm. Rerata tinggi badan perempuan dan laki-laki dengan rumus Chumlea, adalah 154,3±7,03 cm dan 159,1±6,78 cm, dengan perbedaan yang tidak bermakna (p=0,077).Simpulan: Tidak ada perbedaan pengukuran tinggi badan menggunakan microtoise dan rumus Chumlea.